Die Suid-Afrikaanse vrou in landsverdediging - agtergrond en perspektief - E.M. Meyers (Scientia Militaria, 2012)
In the history of South Africa its women always had some role to play in the defence of the country. Women were engaged in military activities even before the institution of the Union Defence Force in 1912. The role of the "Voortrekker" women and also the role of women during the Second War of Independence is referred to as well as their role during both World Wars. The Women's Auxiliary Services originated in 1939 and they played a major role during both war and post war periods. Important to note is the role that the Army Women's College at George played in the renewed militarization of women. The present-day training and utilization of women in the SADF as well as the question of National Service for women are dealt with including detailed arguments for and against the latter. Only one conclusion can be arrived at after having studied all the material and that is that women in uniform have definitely come to stay.